To give or not to give? Choosing chance under moral conflict - LIN, Stephanie C. (Institutional Knowledge at Singapore Management University, 2018)
Although prior research suggests that people should not prefer random chance to determine their outcomes, we propose that in the context of prosocial requests, a contingent of people prefer to rely on chance. We argue that this is because they are conflicted between losing resources (e.g., time, money) and losing moral selfregard. Across five studies, in both choices with binary outcomes (whether to volunteer) and ranges of outcomes (how much to donate), some people preferred to be randomly assigned an outcome rather than to make their own choices. This did not negatively affect prosocial behavior in binary choices and improved prosocial behavior in choices with a range of outcomes. We also found that the preference for a random outcome was stronger when participants felt particularly conflicted. Furthermore, we examined precisely who sorted into the random option. Importantly, choosing the random option decreased moral self-reproach, thus increasing consumer welfare. Our findings speak to consumers’ psychological experience of prosocial requests and suggest an intervention that may increase consumer welfare and prosocial behavior.